Oedema and vasodilatation in inflammation: the relevance of prostaglandins. - Williams, T. J. (BMJ Group, 1977)
The role of prostaglandins in inflammation is still disputed. Some workers have attempted to fit prostaglandins into a simple model, i.e. inflammatory leads to chemical mediator leads to vascular response. Recent work has shown that this approach may be misleading. An alternative model is proposed, involving the interaction of two chemical agents, i.e. a vascular permeability-increasing mediator (such as histamine or bradykinin) and a vasodilator (prostaglandin) which potentiates the plasma exudation produced by the permeability-increasing mediator. The results obtained in testing this model support the further proposal that non-steroidal anti-inflammatory compounds suppress inflammatory swelling by inhibiting vasodilatation.